Pengaruh Limbah Ikan Sebagai Pakan Alami Terhadap Pertumbuhan Ikan Patin (Pangasius Pangasius): Studi Literatur - Firman Syah Putra Waruwu; Ratna Dewi Zebua (Jurnal Ilmu Pertanian dan Perikanan, 2026)
Catfish (Pangasius pangasius) farming continues to grow along with increasing market demand, but is constrained by the high cost of commercial feed, which can reach 60-70% of total production costs. On the other hand, the fish processing industry generates large amounts of waste in the form of heads, viscera, bones, scales, and fins that have the potential to be processed into protein-rich natural feed. This article aims to examine the effect of utilizing fish waste as natural feed on catfish growth based on research results from the last five years. The method used is a literature study by searching national and international scientific articles published between 2021-2026 through the Google Scholar, Garuda, and Sinta-accredited journal databases. The results show that fish waste processed into meal, silage, or fish oil contains high protein and essential fatty acids, which can increase absolute weight gain and specific growth rate, and lower the feed conversion ratio in catfish and several other freshwater fish species. The use of fish waste as natural feed also provides economic benefits in the form of reduced production costs and environmental benefits in the form of reduced pollution from organic waste. Standardization of processing methods and appropriate dosages is needed to optimize the benefits of fish waste as natural feed sustainably.